Resiliência em mães de filhos com Transtorno do Espectro do Autismo-TEA - Silva, Karoline Costa e (2014)
Taking into account Autism Spectrum Disorder, one of the most serious diseases in human development, it is recognized by the stereotypical use and repetitive language besides presence of repetitive behavior and restricted interests which affects social interaction. As such resilience is not being very much studied when it comes to this pathology, this dissertation has the objective to assess the disease towards mothers who have children with Autism Spectrum Disorder (ASD). In the Northeast, Southwest, South and Central East part of Brazil, also aiming in verifying risk factors and mother´s protection in these different regions. The term resilience, here applied, has been applied in the sense of process, where a person, group or community is able to overcome adversity situations turning them into personal development and collective. Instruments used in data collection were through a questionnaire to sum up socio demographic data and resilience scale (WAGNILD e YOUNG,1993), translated and adapted by Pesce et. al(2005). The research has been performed with a sample of 288 mothers, affiliated to Brazilian Institutions that provide assistance to families and children with ASD. The methodology used has been the convenience sampling and theory reference the Resilience construct analysis. General results indicate that mothers, in different regions, present good levels of resilience. Regarding distribution of results in resilience scale, 58,7% of the sampling present moderate resilience, 32,7% high resilience, 8,6% low resilience. There was no statistic relevant difference between general scale result and resilience factors besides regions where participants live. Results show the presence of risk factors and mother´s resilience when dealing with the condition of having a child with ASD. Such findings contribute to the understanding of resilience construct analysis as a process recognized as a phenomenon that takes into account the context the human being is inserted and reveal the importance of individual characteristics in explaining such scenario